Informal urban agriculture : the secret lives of guerrilla gardeners - Hardman, Michael (Urban Agriculture, 2014)
The book explores how unused and under-used urban spaces - from grass verges, roundabouts, green spaces - have been made more visually interesting, and more productive, by informal (and usually illegal) groups known as "guerrilla gardeners".  The book focuses on groups in the English Midlands but the work is set in a broad international context.  We show, through detailed observation and interviews, the differing motivations of groups and individuals involved in trying to produce edible crops on a small scale in the 'forgotten landscapes' of towns and cities.  Some are illegal by design, looking for the thrills - the "naughtiness" as some say - in doing this secretly; but others simply have not obtained the right permissions from land owners.  Guerrilla gardening has usually been presented uncritically, a generic "good thing" - and we present a more critical and balanced evaluation of the activity.  The amount of un- and used-used space is surprisingly high, although the amount of food that can be produced in this way will be relatively small.  However, local involvement in food production, in beautifying the environment even for a short while, can make a lot of difference. Michael Hardman is Lecturer in Geography at the University of Salford, and Peter J. Larkham is Professor of Planning at Birmingham City University.